2011
DOI: 10.5897/ajmr11.548
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and antioxidant activity of purified polysaccharide from cultured Cordyceps militaris

Abstract: The polysaccharide fraction, CM-hs-CPS2, was isolated from fruiting bodies of cultured Cordyceps militaris grown on solid rice medium by hot water extraction and ethanol precipitation, and purified by ion exchange column (DEAE-cellulose-52) and gel filtration column (Sephadex G-100) chromatography. Its structural characterizations were analyzed by gas chromatograph (GC) and fourier transform infrared spectroscopy (FT-IR). Results indicated that CM-hs-CPS2 was a kind of sulfating acidic polysaccharide containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Following the unilateral influence of RTH addition on the soluble dry matter content of the obtained mycelial biomass, it can be seen that the obtained data are statistically assured, registering a significant positive difference compared to the average of experience by 0.24 g soluble dry matter per 100 ml liquid culture medium (Table 2). The results obtained are similar to those presented in the literature for the recipe without the addition of RTH, 2.25 g soluble dry matter / 100 ml liquid culture were determined by Fengyao et al (2011). For the recipe with added RTH no data were found in the literature, but they show significant positive differences for all repetitions performed compared to the recipe without added RTH.…”
Section: Resultssupporting
confidence: 88%
“…Following the unilateral influence of RTH addition on the soluble dry matter content of the obtained mycelial biomass, it can be seen that the obtained data are statistically assured, registering a significant positive difference compared to the average of experience by 0.24 g soluble dry matter per 100 ml liquid culture medium (Table 2). The results obtained are similar to those presented in the literature for the recipe without the addition of RTH, 2.25 g soluble dry matter / 100 ml liquid culture were determined by Fengyao et al (2011). For the recipe with added RTH no data were found in the literature, but they show significant positive differences for all repetitions performed compared to the recipe without added RTH.…”
Section: Resultssupporting
confidence: 88%
“…Previous studies confirmed the ability of the polysaccharide P70-1 and CBP-1 obtained from C. militaris to eliminate hydroxyl radicals [95,96]. The antioxidant activity and the ability to chelate iron ions (Fe2+) were also proven for the polysaccharide designated as CM-hs-CPS2 [97].…”
Section: In Vitro Researchmentioning
confidence: 65%
“…Obviously, the XO inhibitory activity of C. militaris was attributed to their survival strategy to the oxidative stress. For example, several studies showed that polysaccharides from aqueous extracts of C. militaris possessed antioxidant properties [33,34,35] but there was little polysaccharide quantity found in methanolic extracts [25]. Furthermore, the in vitro antioxidant activity was reported to be correlated to cordycepin [21,52] and fatty acids [53].…”
Section: Discussionmentioning
confidence: 99%
“…Yong et al [29] found that hot water extract of C. militaris exhibited significant anti-hyperuricemic action but active components for this activity were not determined. Additionally, the investigation on antibacterial performance of aqueous extracts of C. militaris has been proceeded but bioactive compounds from the methanolic extract have not been elaborated [32,33,34,35]. Infectious diseases caused by bacteria are still the major reason of illness and death in developing countries [36].…”
Section: Introductionmentioning
confidence: 99%